Analisis Perilaku Konsumen terhadap Keputusan Pembelian Sayur Organik CV Golden Leaf Farm Bali - Suardika, I M. Pasek; Ambarawati, I GAA.; Sukaatmadja, I P. (JURNAL MANAJEMEN AGRIBISNIS (Journal Of Agribusiness Management); Vol. 2 - No. 1 - Mei 2014, 2014)
One of the trendy and healthy lifestyle that developed in the community at this time is to go back to nature by consuming organic vegetable products. There are several factors that influence consumer purchasing decisions a product. These factors are the marketing mix consists of product, price, promotion and location as well as psychological consisting of motivation, perception, learning, and the manner in which both factors are external and internal elements. Based on the above explanation, this study aimed to analyze the influence of the marketing  and psychological factors   in organic vegetable purchasing decisions. The research was conducted in CV Golden Leaf Farm Bali as a basic research study place located in the Gobleg village , Banjar district, Buleleng regency, Bali province and at the Supermarket to capture respondents surveyed. The sampling method used was purposive sampling. Number of samples taken by 200 respondents who have ever purchased a minimum of 5 times. Techniques of data collection by means of documentation and interviews. And techniques of data analysis with the help of the program is Visual PLS Version 1.04b1. From these results it can be concluded that in terms of the internal aspects of the psychological factors that consists of motivation, learning, and influence positive attitudes and highly significant organic vegetable purchasing decisions CV Golden Leaf Farm Bali , but the perception, promotion and location does not significantly affect the buying decision of organic vegetables CV Golden Leaf Farm Bali . Considering the promotion of a positive effect it is recommended to CV Golden Leaf Farm Bali to be more active promotion through print media, electronic media, and other media to create a brand image to customers and prospective customers, so the price is not to be sensitive. Similarly, the location, given the location of the positive effect it is recommended to CV Golden Leaf Farm Bali to pay more attention to the existence of the location.
Keywords: Psychological factors, marketing mix, consumer purchasing decisions, organic vegetables